Sirt1 and Sirt6 Mediate Beneficial Effects of Rosiglitazone on Hepatic Lipid Accumulation - Yang, Soo Jin (Public Library of Science, 2014)
BACKGROUND: Sirtuin (Sirt), a sensor of the cell metabolic state, regulates glucose and lipid metabolism. The aim of this study was to address whether rosiglitazone (RGZ) alters hepatic Sirt1 and whether Sirt1 and/or Sirt6 have a regulatory role in the protective effects of RGZ on hepatocyte steatosis. METHODS: To investigate the effect of RGZ on hepatic Sirt1, rats were administered with RGZ for 6 weeks. The involvement of Sirt1/6 in the RGZ-mediated effect against hepatic steatosis was evaluated by single or double knockdown of Sirt1 and Sirt6 in a hepatocyte steatosis model. RESULTS: RGZ in vivo increased Sirt1 expression and its activity in rat livers. In a hepatocyte steatosis model, RGZ significantly reduced lipid accumulation and activated the Sirt1/6-LKB1-AMPK pathway. Sirt1 knockdown abolished the effects of RGZ with regard to hepatocyte fat accumulation and the Sirt1/6-LKB1-AMPK pathway, suggesting that Sirt1 is a key regulator of RGZ-mediated metabolic processes. Sirt6 knockdown inhibited the protective effects of RGZ to a lesser extent than Sirt1, and double knockdown of Sirt1/6 showed no synergistic effects. CONCLUSION: Our results demonstrate that Sirt1/6 are involved in the RGZ-mediated effects on hepatocyte steatosis, and the regulatory effects of Sirt1 and Sirt6 are not synergistic but compensatory for improving hepatocyte steatosis.